Evaluation of the financial performance of the municipalities in Slovakia in the context of multidimensional statistics - Jozef Lukáč; Katarína Teplická; Katarína Čulková; Daniela Hrehová (Journal of Risk and Financial Management, 2021)
In some studies, only financial aspects are emphasized, but we also see cases of assessing the financial health of municipalities through socio-economic indicators. Public organizations worldwide have had to increase their financial performance by adopting management practices. Nonetheless, financial performance might be mostly predicted by contingencies that are not within direct managerial control. The purpose of this paper is to identify clusters of municipalities on the basis of agglomerate cluster analysis, the results of which will point to the financial situation of the municipalities in the selected region. The main aim of this contribution is to identify the location of the municipalities of the chosen self-governing region of Slovakia using the clustering method by selected financial indicators. Individual clusters have similar properties and they differ from the characteristics of businesses in other clusters. The results show that organizational and environmental contingencies affect financial performance, but a significant amount of variation in financial performance is unexplained-indicating that management creates better financial health in the municipality and creates a clearer budget for the management, employees, and residents of the municipality.
Keywords: 330; financial performance; administration; cluster analysis; financial indicators; Slovakia